2020
DOI: 10.5195/ijms.2020.669
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice Associated with COVID-19 Among School Students in Bharatpur, Chitwan District of Nepal

Abstract: Background: The emergence of the novel Coronavirus in December 2019 from Wuhan, China, now named SARS-COV-2, which causes COVID-19 disease has now reached the pandemic level. The ongoing pandemic has already infected more than fifteen million people and over hundred thousand people around the world has died. The knowledge, attitude, and practice (KAP) of people towards this disease is important to understand to limit its transmission. Methods: A purposive cross-sectional study was conducted among 101 sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 12 publications
10
15
1
Order By: Relevance
“…Surprisingly, despite very good commitment to face mask and hand cleaning at school entry but a significant percentage of children took off their masks during the school day (41.5%) and didn't use hand cleaner (28.1%), these findings indicated that children in that age need more intimate supervision and more frequent health education about the importance of protective measures. similar results were noted by Singh et al (21) who found that 98.7% used frequent hand washing or alcohol-based cleanser to protect against COVID-19 while relatively lower value was found by Subedi et al (20) , 77.23%reported using face mask, as previously mentioned, this difference may be explained by variation of socio-demographic criteria, cultural background, and economics in different communities.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Surprisingly, despite very good commitment to face mask and hand cleaning at school entry but a significant percentage of children took off their masks during the school day (41.5%) and didn't use hand cleaner (28.1%), these findings indicated that children in that age need more intimate supervision and more frequent health education about the importance of protective measures. similar results were noted by Singh et al (21) who found that 98.7% used frequent hand washing or alcohol-based cleanser to protect against COVID-19 while relatively lower value was found by Subedi et al (20) , 77.23%reported using face mask, as previously mentioned, this difference may be explained by variation of socio-demographic criteria, cultural background, and economics in different communities.…”
Section: Resultssupporting
confidence: 83%
“…The relatively lower rate of hand washing after coughing or sneezing, before eating, and on touching any surface in the current work may be due to the fact that it measures hand washing practice in schools while Xue et al (18) and Shehata et al (19) performed their study on school students during the period of school closure after the beginning of the pandemic, as the children at home had better access to hand washing than in school and they replace it with the use of alcoholbased hand cleaners. Subedi et al (20) found a relatively lower percentage, as 79.21% of students adopted handwashing measures as a preventive strategy; the difference in these values reflected variation between different localities in the perspective of awareness and willingness of the community about COVID-19 prevention.…”
Section: Resultsmentioning
confidence: 99%
“…16 A study suggested that Nepalese students had good level of knowledge about COVID-19. 17 Another study emphasized that > 90% of participants were aware of agent, route of transmission and symptoms of COVID-19 and 75 % had knowledge on serious outcome in underlying clinical conditions. 18 Globally social distancing is the most compelling approach to reduce respiratory virus transmission in community.…”
Section: Resultsmentioning
confidence: 99%
“…More than 75.0% of participants had good knowledge about COVID-19 agents, main symptoms and reasoning of isolation. A study has suggested that Nepalese students had good knowledge of COVID-19 [ 27 ]. Also, another study emphasized that >90.0% of participants were aware of the agent, route of transmission and clinical symptoms and 75.0% had knowledge about serious outcomes of COVID-19 in underlying clinical conditions [ 28 ].…”
Section: Discussionmentioning
confidence: 99%